Contextualizing Collaborative Learning: A Comparative Study of Urban and Rural Senior High School Students’ Performance in Circle Theorems - Dapaah Boatemaa , Akua; Dissou Arthur, Yarhands; Appiagyei, Ebenezer; Adu Obeng, Benjamin (International Journal of Mathematics and Mathematics Education, 2026)
Purpose – This study investigated whether school location moderates students’ achievement in Circle Theorems when instruction is delivered through collaborative learning in Ghanaian senior high schools. Although collaborative learning is frequently linked to improved mathematics achievement, evidence on its effectiveness across contrasting Ghanaian school contexts remains limited. Methodology – Guided by Social Constructivist learning theory, the study employed a quantitative, quasi-experimental design. Two schools were purposively selected: one urban (School A) and one rural (School B). The sample comprised 152 students (n = 76 per school), with intact classes assigned as experimental and control groups. After the instructional intervention, data were collected using a 20-item multiple-choice Circle Theorems test. An independent-samples t-test was used to compare post-test performance of students taught via collaborative learning across the two locations. Findings – Results showed no statistically significant difference in Circle Theorems achievement between students in the rural and urban schools exposed to collaborative learning. This indicates that collaborative learning, when implemented effectively, produces comparable learning outcomes across settings, suggesting limited contextual influence. The findings support the scalability of collaborative learning as an equity-oriented instructional approach in geometry. Novelty – The study contributes original, context-sensitive evidence by directly comparing the effects of collaborative learning on Circle Theorems achievement across rural and urban Ghanaian senior high schools, addressing a gap in local geometry education research. Significance – Mathematics teachers, curriculum developers, and policymakers may use these findings to justify wider adoption of collaborative learning to strengthen conceptual understanding in geometry and promote equitable achievement across diverse school environments.